2015
DOI: 10.1515/njmr-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries of National Belonging in Ingrian Finnish Return Migration: <i>A Multi-level Perspective</i>

Abstract: This study examines the discursive construction of Finnishness within the context of Ingrian Finns' return migration from Russia to Finland. The focus is on how characteristics of Finnishness, especially ancestry and language, are employed at institutional, community and interpersonal levels of text and talk. The results show how the same characteristics can be used to both in-and exclude Ingrian Finns from the national ingroup, and how essentialist notions of ethnonational belonging can be used strategically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Over these 20 years, the qualifications for returning migrants became increasingly restrictive, and at the beginning of the 2010s the application queue was closed (e.g., Varjonen, Arnold & Jasinskaja-Lahti 2013;Mähönen et al 2015;Prindiville & Hjelm 2018).…”
Section: Ingria and Ingrian Finnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over these 20 years, the qualifications for returning migrants became increasingly restrictive, and at the beginning of the 2010s the application queue was closed (e.g., Varjonen, Arnold & Jasinskaja-Lahti 2013;Mähönen et al 2015;Prindiville & Hjelm 2018).…”
Section: Ingria and Ingrian Finnsmentioning
confidence: 99%
“…After this brief and inevitably reductive description we are obliged to remark that labels such as "Ingrian Finn," "Ingrian," and "Finn," as well as their links to identities, are somewhat ambiguous and bound to socio-historical contexts (e.g., Anepaio 1999;Hakamies 2004;Varjonen, Arnold & Jasinskaja-Lahti 2013;Mähönen et al 2015;also Raudalainen 2004). In the Soviet Union, the Finnish-speaking population -including people living in Ingria -were typically labeled and self-identified as "Finns.…”
Section: Ethnologia Europaeamentioning
confidence: 99%
“…A relevant comparative survey conducted among immigrants in 14 Western states found that Finnish citizenship was considered to entail least national belonging to its bearers (Simonsen 2017:9). Similarly, interview studies with Ingrian Finns who moved to Finland from Russia as (ethnic) repatriates after 1990 suggest that for the Finnish majority the language and ancestry are important markers of "Finnishness," making it very difficult for immigrants to adapt (Varjonen, Arnold, and Jasinskaja-Lahti 2013;Mähönen et al 2015).…”
Section: Expanded and Limited Membershipmentioning
confidence: 99%
“…In 1990 Soviet nationals of Finnish descent, 'Ingrian Finns' 1 who were displaced in the post-Second World War Soviet Union, got the right to apply for repatriation status. While Finland expected to receive 'Finns' through this repatriation programme, many of the returnees were perceived as 'Russians' who were not considered Finnish enough and deemed to have problems with 'integration' (Mähönen, Varjonen, Prindiville, Arnold, & Jasinskaja-Lahti, 2015). In addition, researchers have argued that since the fall of the socialist system in the 1990s, Eastern and Central Europe has been portrayed as underdeveloped and as being the Other in relation to Western Europe (Mulinari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%